Impact response of thick composite plates under uniaxial tensile preloading. (March 2015) - Guillaud, N.; Froustey, C.; Dau, F.; Viot, P.
Abstract: This work focuses on the impact response of composite plates 5 mm thick subjected to uniaxial tension preload. Laminated carbon/epoxy with quasi-isotropic stacking sequence ( [ 0 / 45 / 90 / - 45 ] 2 ) S samples were used. Doehlert-type design of experiments was proposed to investigate the influence of both preload and impact energy on impact composite responses. Deformation, varying from 300 to 3000 micro-strain, was imposed thanks to a preload device designed for this purpose. Impacts were generated using a home made drop tower. Imposed impact energy was varying from 30 to 214 J. Post-impact damage was characterized by both non-destructive (ultrasound) and destructive (deply) techniques. Influence of the preloading on delamination areas (total and projected) was quantified and found sensitive to the preloading.